The roadmap of bioeconomy in China. Issue 4 (30th November 2022) - Zhang, Xu; Zhao, Cuihuan; Shao, Ming‐Wei; Chen, Yi‐Ling; Liu, Puyuan; Chen, Guo‐Qiang
Abstract: The bioeconomy drives the development of life science and biotechnology as a blueprint for the future development of human society, and offers a cross‐cutting perspective on the societal transformation towards long‐term sustainability and the transition away from the non‐renewable economy. Moreover, the sustainable bioeconomy strategies are consistent with the United Nation's (UN) Sustainable Development Goals (SDG) and are becoming the centre of the achievement for SDG. The Chinese '14th Five‐Year Plan for Bioeconomy Development' (2021–2025), including the development goals of China's bioeconomy containing biomedicine, agriculture, bio‐manufacturing and bio‐security as a strategic priority, is discussed. The plan offers three pathways to improve bioeconomy, including technological innovation, industrialisation and policy supports. Finally, it concludes China's first bioeconomy development plan as a success, suggesting the key role of industrial biotechnology in bioeconomy. Abstract : This paper discusses the Chinese '14th Five‐Year Plan for Bioeconomy Development' (2021–2025), including the development goals of China's bioeconomy containing biomedicine, agriculture, bio‐manufacturing and bio‐security as a strategic priority. The plan offers three pathways to improve bioeconomy including technological innovation, industrialisation and policy supports. China's first bioeconomy development plan as a success, suggesting the key role of industrial biotechnology in bioeconomy.